How (not) to draw philosophical implications from the cognitive nature of concepts: the case of intentionality - Iijima, Kazuki; Ota, Koji (Frontiers in Psychology, 2014)
Philosophers have often appealed to intuitive judgments in various thought experiments to support or reject particular theses. Experimental philosophy is an emerging discipline that examines the cognitive nature of such intuitive judgments. In this paper, we assess the methodological and epistemological status of experimental philosophy. We focus on the Knobe effect, in which our intuitive judgment of the intentionality of an action seems to depend on the perceived moral status of that action. The debate on the philosophical implications of the Knobe effect has been framed in terms of the distinction between the competence and performance of the concept of intentionality. Some scholars seem to suggest that the Knobe effect reflects the competence (or otherwise, the performance error) of the concept of intentionality. However, we argue that these notions are purely functional and thus do not have philosophical implications, without assuming normativism, which we see as problematic in a psychological methodology. Finally, focusing on the gap between competence and rationality, we suggest future directions for experimental philosophy.